Impact of COVID-19 on antenatal care utilization-a tertiary care center study in New Delhi - Maan, Garima; Dhiman, Niharika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The COVID19 pandemic has impacted people’s daily lives all around the world. A lack of resources caused by COVID19 has put many health systems under pressure and sparked protest from many quarters. As COVID19 care was the primary focus of the majority of Delhi’s healthcare delivery facilities, several staff members became positive, staff members became involved in COVID19 emergency duties, and staff members were forced into mandatory quarantines, which limited the provision of antenatal care to routine care. The aim of this study was to know the impact of COVID-19 on routine antenatal care utilization. Methods: This was a questionnaire-based study was conducted in the Department of Obstetrics and Gynecology in MAMC and Lok Nayak Hospital New Delhi, between December 2020 to May 2021 over a period of 6 months. A total of 55 antenatal cases who fulfilled the inclusion and exclusion criteria were included in the study presenting to hospital over a period of 6 months. Results: Only 12% women were booked, 23% women had fear of getting infection, all routine investigation were done in only 14.5% women, 20% women had travel difficulties, 50% women missed their first trimester visit, 50.9% women could get the anomaly scan done. Conclusions: The COVID-19 had a substantial impact on antenatal care, delaying the diagnosis, travel to the medical facility, and subsequent treatment. Age of the mother, suspension and diversion of maternity health care, fear of the COVID-19 pandemic, lack of family support, and transportation accessibility were all important factors that affected how little antenatal care pregnant women used.